Common fixed points of maps on fuzzy metric spaces - S. N. Mishra; Nilima Sharma; S. L. Singh (International Journal of Mathematics and Mathematical Sciences)
Following Grabiec's approach to fuzzy contraction principle, the purpose of this note is to obtain common fixed point theorems for asymptotically commuting maps on fuzzy metric spaces.